2017
DOI: 10.1213/ane.0000000000002433
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Approach to the Prescription Opioid Epidemic in Orthopedic Surgery

Abstract: Orthopedic surgery is associated with significant perioperative pain. Providing adequate analgesia is a critical component of patient care and opioids play a vital role in the acute postoperative setting. However, opioid prescribing for patients undergoing orthopedic procedures has recently been identified as a major contributor to the current opioid epidemic. As opioid usage and related morbidity and mortality continue to rise nationwide, opioid-prescribing practices are under increased scrutiny. Here, we upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 50 publications
1
97
0
1
Order By: Relevance
“…28 Although not fully understood, narcotic prescription patterns among orthopaedic surgeons may be playing a critical role in the prolonged utilization of narcotics. [29][30][31] As such, this is a potentially preventable situation as we believe that the majority of patients with ulnar sided wrist pain from UIS are not typically prescribed narcotics for preoperative pain relief. This is very evident given newly published level 1 data that showed no benefit from opioid consumption for chronic orthopaedic conditions such as low back and knee pain.…”
Section: Demographic and Socioeconomic Factorsmentioning
confidence: 99%
“…28 Although not fully understood, narcotic prescription patterns among orthopaedic surgeons may be playing a critical role in the prolonged utilization of narcotics. [29][30][31] As such, this is a potentially preventable situation as we believe that the majority of patients with ulnar sided wrist pain from UIS are not typically prescribed narcotics for preoperative pain relief. This is very evident given newly published level 1 data that showed no benefit from opioid consumption for chronic orthopaedic conditions such as low back and knee pain.…”
Section: Demographic and Socioeconomic Factorsmentioning
confidence: 99%
“…Different surgical specialties have shown that decreasing opioid prescribing in the postoperative setting is possible when protocols and standardized prescribing regimens are implemented . Preoperative education, preoperative risk stratification, procedure‐based pain thresholds, standardized prescribing regimens, and postoperative analysis are all components of a comprehensive pain management protocol.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple opportunities for the anesthesiologist, surgeon, and institution to reduce opioid exposure and minimize patient harm. 16,31,33 The best-characterized clinical strategies include the use of multimodal analgesia (MMA) and enhanced recovery after surgery (ERAS) initiatives to standardize care and improve outcomes while providing satisfactory perioperative pain control. MMA has been consistently demonstrated to minimize opioid consumption and related side effects and is considered a vital component of ERAS pathways.…”
mentioning
confidence: 99%